THE ROLE OF HEALTH ADMINISTRATION IN EMERGENCY HEALTH CRISES - Ali Mohammed Eid Alotabi; Yaser Mohammad Alhindi; Abdullah Ibraheem Abdullah Almootah; Amin Obaid Alhindi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Health administration plays a critical role in managing emergency health crises, ensuring effective response, and safeguarding public health. This paper explores the role of health administration in emergency health crises and examines the methods, results, and implications of its involvement. By analyzing the challenges faced by health administrators during emergencies and discussing strategies for improvement, this paper highlights the importance of effective leadership and coordination in crisis response.